INCREASING GRAIN ZINC AND YIELD OF WHEAT FOR THE DEVELOPING WORLD: A REVIEW - Hussain, Shahid; Maqsood, Muhammad Aamer; Rahmatullah, Mr (Emirates Journal of Food and Agriculture, 2017)
Hunger and zinc (Zn) malnutrition are major health risk factors in the developing countries. Wheat is a major staple food in the world but it is inherently low in grain Zn concentration especially when grown on Zn deficit calcareous soils. Therefore, producing Zn enriched wheat grains at the farmers' fields is the best solution against human Zn deficiency. Biofortification approaches include selection, improvement and management of cultivated wheat genotypes to ensure optimum grain Zn concentration for human consumption. Soil and foliar application of Zn to wheat grown on Zn deficient soils enhances both the grain yield and grain Zn concentration. Genotype screening for higher grain yield and grain Zn concentration is prerequisite to ensure adoptability of poor farmers to newly developed genotypes for Zn biofortification. Conclusively, simultaneous consideration of grain yield and grain Zn concentration of wheat is the sustainable and economical approach to achieve our food targets.